Influence of silk–silica fusion protein design on silica condensation in vitro and cellular calcification. Issue 26 (23rd February 2016) - Plowright, Robyn; Dinjaski, Nina; Zhou, Shun; Belton, David J.; Kaplan, David L.; Perry, Carole C.
Abstract : Peptide location in silk–R5 genetic chimeras (N vs. C terminus) moderates cellular calcification and influences silicification through entropically driven protein aggregation. Abstract : Biomaterial design via genetic engineering can be utilized for the rational functionalization of proteins to promote biomaterial integration and tissue regeneration. Spider silk has been extensively studied for its biocompatibility, biodegradability and extraordinary material properties. As a protein-based biomaterial, recombinant DNA derived derivatives of spider silks have been modified with biomineralization domains which lead to silica deposition and potentially accelerated bone regeneration. However, the influence of the location of the R5 (SSKKSGSYSGSKGSKRRIL) silicifying domain fused with the spider silk protein sequence on the biosilicification process remains to be determined. Here we designed two silk–R5 fusion proteins that differed in the location of the R5 peptide, C- vs. N-terminus, where the spider silk domain consisted of a 15mer repeat of a 33 amino acid consensus sequence of the major ampullate dragline spidroin 1 from Nephila clavipes (SGRGGLGGQG AGAAAAAGGA GQGGYGGLGSQGT). The chemical, physical and silica deposition properties of these recombinant proteins were assessed and compared to a silk 15mer control without the R5 present. The location of the R5 peptide did not have a significant effect on wettability and surface energies, while the C-terminal location of the R5 promoted more controlled silica precipitation, suggesting differences in protein folding and possibly different access to charged amino acids that drive the silicification process. Further, cell compatibility in vitro, as well as the ability to promote human bone marrow derived mesenchymal stem cell (hMSC) differentiation were demonstrated for both variants of the fusion proteins.